Managing educational technology : school partnerships & technology integration - Abrams, Sandra Schamroth; Chen, Xiaojun; Downton, Michael Paul (Routledge, 2018)
Managing Educational Technology examines the ways in which stakeholders from businesses, K-12 schools, and universities can influence the quality and success of technology integration in primary and secondary classrooms.? Inspired by their experiences in the field as educators, education researchers, and technology evaluators, the authors present vignettes that highlight the benefits, demands, and limitations often associated with the introduction and integration of educational technologies to K-12 school environments. These examples also underscore the inherent nuances in partnerships among businesses, K-12 schools, and universities. Readers can use these rich examples when considering ways to integrate products into schools, as well as when discussing, analyzing, and evaluating the promises of and challenges in doing so. End-of-chapter questions guide readers to consider alternate actions and identify steps for additional growth, which complement the authors' practical suggestions to strengthen business-school-university partnerships.- Resumé vydavatel
Keywords: didaktická technika; průmysl; vzdělávání; educational technology; industries; education; elektronické knihy; monografie; electronic books; monographs